2008
DOI: 10.1021/nl071180e
|View full text |Cite
|
Sign up to set email alerts
|

Multisegment Nanowire Sensors for the Detection of DNA Molecules

Abstract: We describe a novel application for detecting specific single strand DNA sequences using multisegment nanowires via a straightforward surface functionalization method. Nanowires comprising CdTe−Au−CdTe segments are fabricated using electrochemical deposition, and electrical characterization indicates a p-type behavior for the multisegment nanostructures, in a back-to-back Schottky diode configuration. Such nanostructures modified with thiol-terminated probe DNA fragments could function as high fidelity sensors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(68 citation statements)
references
References 43 publications
1
66
0
1
Order By: Relevance
“…그 중 나노선 구조는 여러가지 물질을 나노단위 두께의 선형태로 성장시킨 구조로써, 표면적이 크다는 구조적인 특성상 센서, [3][4][5][6][7][8][9] 태양전지, 10-12) 의료 [13][14][15][16] …”
Section: -2)unclassified
“…그 중 나노선 구조는 여러가지 물질을 나노단위 두께의 선형태로 성장시킨 구조로써, 표면적이 크다는 구조적인 특성상 센서, [3][4][5][6][7][8][9] 태양전지, 10-12) 의료 [13][14][15][16] …”
Section: -2)unclassified
“…[1] The emerging trend for point-of-care instrumentation is driving the development of miniaturized systems capable of reliable and rapid quantification of a wide range of biomolecules. [2][3][4][5] To address this opportunity, nanosensors based on one-dimensional nanostructures such as silicon nanowires and carbon nanotubes FET devices are being explored since these nanostructures offer the potential to achieve highly sensitive integrated sensors with direct electrical readout. [6][7][8] In these sensor systems, the perturbation in the local electrostatic environment of a nanowire-based FET by a charged analyte alters the conductance, which is employed as the sensor signal.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Nanowires represent a new and emerging powerful class of sensors and to date have been utilized for direct, sensitive and rapid detection of biological and chemical species. [2,3,[11][12][13][14] Noble metal nanowires such as gold, platinum and silver, are of particular importance due to their excellent 1 To whom any correspondence should be addressed. …”
Section: Introductionmentioning
confidence: 99%
“…Various electrochemical sensing platforms based on namomaterials such as carbon nanotubes (Zhang et al, 2009a,b;Zhu et al, 2009), nanoparticles (Das and Yang, 2009;Du et al, 2009;Li et al, 2009) and nanowires (Chen et al, 2009;Wang and Ozkan, 2008) have been reported. These studies indicate that nanomaterials are making a big impact on development of electrochemical biosensors and nanotechnology is bringing new possibilities for improving both the sensitivity and selectivity of biosensing devices.…”
Section: Introductionmentioning
confidence: 99%